2,4-Diphenyl-3-azabicyclo[3.3.1]nonan-9-one Semicarbazone as a Chromogenic Reagent for Vanadium(V) - Thanikachalam, V.; Manivarman, S.; Jayabharathi, J. (Asian Journal of Chemistry, 2016)
Spectrophotometric determination of vanadium(V) was carried out using 2,4-diphenyl-3-azabicyclo[3.3.1]nonan-9-one semicarbazone in aqueous acetic acid medium at 30 ± 0.1°C. Beer's law is obeyed in the concentration ranging from 10-52 ppm and molar absorptivity is 747 dm3 mol-1 cm-1 with sensitivity 0.068 μg cm-2 at 910 nm. Most of the anions and cations did not interfere except copper and tartrate. The composition of the complex is found to be 1:1 (metal:ligand) and stability of the complex is determined to be 2.4 × 103.